2001
DOI: 10.1088/0964-1726/10/1/309
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheological fluid damper feedback linearization control for helicopter rotor application

Abstract: This study explores the possible use of a magnetorheological (MR) damper with feedback linearization control law for helicopter lag damping applications. Since this control law is based on an assumed damper model, the helicopter may be susceptible to limit cycle instabilities in the presence of model errors due to uncertainties (even if the prescribed damping using feedback linearization control is greater than the system negative damping). For specified uncertainty bounds, a robust control law can be synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 9 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…These devices have small and large scale applications depending on their dimensions. Typically, Small MR damper forces range around 1000 N and have been used, among others, as shock absorbers for vehicle's and motorcycle's suspension Poynor (2001); Gravatt (2003), cars seat suspension Choi et al (2000), vibration control in helicopters rotors F. Gandhi and Xia (2001) and prosthetic limbs J.D. Carlson and Toscano (2001).…”
Section: Introductionmentioning
confidence: 99%
“…These devices have small and large scale applications depending on their dimensions. Typically, Small MR damper forces range around 1000 N and have been used, among others, as shock absorbers for vehicle's and motorcycle's suspension Poynor (2001); Gravatt (2003), cars seat suspension Choi et al (2000), vibration control in helicopters rotors F. Gandhi and Xia (2001) and prosthetic limbs J.D. Carlson and Toscano (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The device uses the typical property of controllable magnetorheological fluids: when exposed to a magnetic field, it can change in milliseconds its characteristics from a linear viscous fluid to a semisolid state. The literature reports many applications of MR dampers in several engineering fields, including mechanics, aerospace and robotic [26], and also biomedical [27] and civil engineering [28]. The prototype of the MR damper is the RD-1005-3 model, produced by the Lord Corporation.…”
Section: Description Of the Test Set-up Andmentioning
confidence: 99%
“…Magnetorheological fluids consist of micro-sized, magnetically polarisable particles dispersed in a carrier medium such a silicon or mineral oil [10]. When a magnetic field is applied to the fluid, particle chains form and the fluid becomes semi-solid displaying viscoplastic behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…When a magnetic field is applied to the fluid, particle chains form and the fluid becomes semi-solid displaying viscoplastic behaviour. Changes in the applied magnetic field leads to changes in the damper force hence improving the adaptability characteristics [10]. Laboratory work has shown that lag damper versions of MRFE dampers also have amplitude-and frequencydependent behaviour [13], [12].…”
Section: Introductionmentioning
confidence: 99%